A comunicação nas redes sociais e os transtornos depressivos: um olhar à luz da Psicanálise Winnicottiana - Balão, Sonia Maria da Silva (2018)
Nowadays, a great number of young people present themselves in clinic with complaints of a lonely and isolated personal life, with an affective-social withdrawal and impoverishment, sadness, hopelessness, anguish, internal guilt, helplessness, lack of will to live, cranky, self agressive and self-multilation behaviors. These factors, beyond worrying, point to pathology and to complex emotional difficulties. Another common feature of these young patients is to dedicate a lot of time to the virtual world instead of real life. On the social network, they have a group of lots of friends and dedicate a lot of their time with unknown people. This clear dissociation between the cloistered real life and the active virtual life demands questioning the social network role and think its excessive use as a way of psychological defense. Therefore, through the case study of a 16 years old young woman (when she begins the analysis), this research project proposes to understand this dissociation and its possible relation of the phenomenon to some psychopathology, specially depression, covering the contradictory way of the young people to have a depressive, apathetic and isolated existence in real life and manifest themselves vitally, interactively and intensely in social networks. The theorical basis of this investigation is the Winnicott’s Theory of Personal Maturity and the focus was on the articulation between the clinical case and the theory through the theoretical-methodological research and the research-listening. Reports from the patience, written by the psychologist during her three first years of psychological treatment and WhatsApp and Facebook messages given by the patience were all the valid corpus for this investigation. By avoiding contact with the loneliness that her illness aroused, the patient presented herself to treatment incapacitated to be alone and think about herself. Because of the lack of limits, she made use of the virtual world and isolated herself from shared reality. With psychic action from the analytic process, she started to stay connected to the cyber world while she needs, returning to the real world whenever she feels strengthened. Therefore, based on the analysis of the results of this clinical case, the use of communication in social networks by young depressive people is based on a paradox: the defense of the maniac type by the performance of the false self, to avoid depressive psychopathology, and, at the same time, the attempt to be cured by the new possibilities when the patient can experience the false self in consigning thru it the emersion of the true self